Pendampingan Digital Marketing terhadap UMKM Moya Juice Sebagai Sarana Promosi - Ita Purnama; Irwaty Irwaty; Yuliani Fitari; Nur Afni (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
MSMEs (Micro, Small, and Medium Enterprises) play a crucial role in the Indonesian economy, especially in creating jobs and driving local economic growth. but often face challenges in digital product marketing. MSMEs are a type of business that has a very large influence on economic development and also needs to experience progress in the field of technology, especially in marketing products. The purpose of this mentoring activity is to develop digital marketing capacity in MSMEs in order to expand marketing networks and disseminate product information more widely and effectively. One of the MSMEs targeted in this activity is Moya Juice, a local beverage business that needs guidance in digital marketing strategies. The approach used in this activity consists of four main stages, namely: (1) initial survey to understand the conditions and needs of MSMEs, (2) socialization regarding the concept and importance of digital marketing, (3) direct assistance in digital marketing practices such as content creation, social media management and (4) ongoing maintenance and evaluation to ensure optimal implementation. Through this form of community service, it is hoped that MSMEs can develop their business potential and build marketing networks that are no longer limited to the local market, but are able to reach regional to national markets.